Epitypification, cytology, genetic and physiological variability, and genomic analysis of Puccinia psidii - Machado, Patrícia da Silva (2015)
In this study, the epitype of Puccinia psidii Winter from Psidium guajava was designed to serve as reference for future taxonomic and molecular studies of the fungus. This rust is it considered autoecious and macrocyclic, but lacking pycnium and with little knowledge about the formation, nuclear condition and the role of basidiospores in the life cycle of P. psidii. Thus, cytological studies showed that after nuclear fusion the diploid nucleus migrated into the metabasidium and underwent meiotic division resulting in four haploid nuclei. Septum was formed between each nucleus, which can undergo mitotic division and result in four basidiospores mainly binucleate. After inoculations on detached leaves of Syzygium jambos, rudimentary lobate apressoria were observed, but with no evidence of penetration and infection. In another study, six microsatellite markers were used to analyze the genetic variability of 79 isolates of P. psidii collected from different hosts in Australia, New Caledonia and China. Up to now it was found that isolates are genetically uniform, except for a few point mutations in four isolates from Australia. Although the correlation is low (p <0.01, r = 0.061), there was an association between the genetic variability of isolates of P. psidii from Brazil, estimated by microsatellites, and the results of cross-inoculation on different Myrtaceae species. Genome sequencing of five isolates of Puccinia psidii from Brazil and Australia and a brief genomic analysis among them was provided. The assembly of each isolate was compared to VIC 42496. The analysis reveled that more than 70% of the contigs of xeach isolate that was not present on assembly of VIC42496 had no significant homology (no hits) to anything currently residing in the fungal genome databases. For those contigs that displayed similar to fungal sequences, including P. psidii, only three contigs matched with genes coding for products that could be involved in pathogenicity.